Method for preparing long-term color-stable superabsorbent polymer particles

By adding hydrogen peroxide before crosslinking after hot surface and using specific crosslinking agents and chelating agents, the problem of color instability of superabsorbent polymer particles under high temperature and high humidity conditions is solved, and long-term color stability and high absorption are achieved performance.

CN113166430BActive Publication Date: 2024-12-24BASF SE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980069050.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-10-29
Filing Date
2019-10-23
Publication Date
2024-12-24
Estimated Expiration
2039-10-23

AI Technical Summary

Technical Problem

Superabsorbent polymer particles tend to discolor under high temperature or high humidity conditions, resulting in unstable color, especially in tropical or subtropical countries where they often turn yellow or brown, affecting their aesthetics and consumer acceptance.

Method used

0.014 to 0.095% by weight of hydrogen peroxide is added to the polymer particles prior to post-crosslinking of the hot surface and the preferred crosslinking agent and chelating agent are used during post-crosslinking of the hot surface to control the crosslinking agent and hydrogen peroxide. The amount of hot surface is subjected to post-crosslinking and cooling treatment.

Benefits of technology

It significantly improves the long-term color stability of superabsorbent polymer particles, ensures that the absorption and centrifugal retention capacity are maintained under high loads, and at the same time reduces the yellowness index, ensuring that the color of the product remains unchanged during storage and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_12
    Figure SMS_12
  • Figure SMS_14
    Figure SMS_14
  • Figure SMS_19
    Figure SMS_19
Patent Text Reader

Abstract

The present invention relates to a process for producing long-term color-stable superabsorbent polymer particles, which comprises polymerization of a monomer solution, drying the resulting polymer gel, optionally grinding and classifying the resulting dried polymer gel, and thermal surface postcrosslinking and cooling the resulting polymer particles, wherein a thermal surface postcrosslinker and hydrogen peroxide are added to the polymer particles before the thermal surface postcrosslinking.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to a process for producing long-term color-stable superabsorbent polymer particles, which comprises polymerization of a monomer solution, drying the resulting polymer gel, optionally grinding and classifying the resulting dried polymer gel, and thermal surface postcrosslinking and cooling the resulting polymer particles, wherein a thermal surface postcrosslinker and hydrogen peroxide are added to the polymer particles before the thermal surface postcrosslinking.

[0002] Superabsorbent polymer particles can be used not only to prepare diapers, tampons, sanitary napkins and other hygiene products, but also as water retaining agents in market gardening. Superabsorbent polymer particles are also often referred to as "absorbent resins", "superabsorbents", "superabsorbent polymers", "absorbent polymers", "absorbent gelling materials", "hydrophilic polymers" or "hydrogels".

[0003] The preparation of superabsorbent polymer particles is described in the monograph "Modern Superabsorbent Polymer Technology", FL Buchholz and AT Graham, Wiley-VCH, 1998, pages 71-103.

[0004] The properties of the superabsorbent polymer particles can be adjusted, for example, by the amount of crosslinker used. As the amount of crosslinker increases, the centrifuge retention capacity (CRC) decreases and at 21.0 g / cm 2 The absorption under pressure (AUL) passes through a maximum value.

[0005] To improve application properties such as the permeability of the swollen gel bed in diapers (SFC) and the 2 Absorption under pressure (AUHL), the superabsorbent polymer particles are usually surface post-crosslinked. This increases the degree of crosslinking on the particle surface, which allows 49.2 g / cm 2 The correlation between the absorption under pressure (AUHL) and the centrifuge retention capacity (CRC) is at least partially eliminated. The surface post-crosslinking can be carried out in the aqueous gel phase. However, it is preferred that the dried, ground and sieved polymer particles (base polymer) are surface coated with a surface post-crosslinker, thermally surface post-crosslinked and dried. Crosslinkers suitable for this purpose are compounds that can form covalent bonds with at least two carboxyl groups of the superabsorbent polymer particles.

[0006] A frequently occurring problem in superabsorbent polymer particles is discoloration, which occurs during storage at elevated temperatures or high air humidity. In tropical or subtropical countries, such a situation often occurs during storage. Under such conditions, the superabsorbent polymer particles turn yellow; they can even appear brown or almost black. This discoloration of the practically colorless superabsorbent polymer particles is unsightly and undesirable, since it is visible especially in the desired thin hygiene articles, and consumers reject unsightly hygiene articles. The causes of the discoloration have not yet been fully elucidated, but reactive compounds (e.g. residual monomers in the polymerization reaction), the use of certain initiators, impurities in the monomers or neutralizers, surface postcrosslinkers or stabilizers used in the monomers may play a role.

[0007] EP 1 770 113 A1 discloses surface postcrosslinking in the presence of peroxides in order to reduce residual monomers.

[0008] WO 2006 / 062258 A2 discloses a method of surface post-crosslinking by adding a water-soluble polymerization initiator and irradiating the mixture with active energy rays. This method does not require any heating.

[0009] WO 2010 / 096595 A2 discloses superabsorbent polymers having antimicrobial properties. The superabsorbent polymer is coated with 0.5 to 20% by weight of hydrogen peroxide and dried.

[0010] EP 2 915 548 A1 discloses a process for preparing superabsorbent particles which comprises adding a peroxide after the polymerization.

[0011] It is an object of the present invention to provide a process for preparing superabsorbent polymer particles having improved long-term color stability.

[0012] This object is achieved by a process for preparing long-term color-stable superabsorbent polymer particles, which comprises the polymerization of a monomer solution comprising:

[0013] a) partially neutralized acrylic acid,

[0014] b) optionally at least one cross-linking agent, and

[0015] c) at least one initiator;

[0016] The resulting polymer gel is dried; the resulting dried polymer gel is optionally ground and classified, and the resulting polymer particles are subjected to thermal surface postcrosslinking and cooling, wherein a thermal surface postcrosslinker and 0.014 to 0.095% by weight of hydrogen peroxide, based on the polymer particles, are added to the polymer particles before the thermal surface postcrosslinking.

[0017] The thermal surface postcrosslinkers are added to the polymer particles before the thermal surface postcrosslinking in an amount of preferably 0.005 to 5% by weight, more preferably 0.010 to 2% by weight, most preferably 0.015 to 1% by weight, based on the polymer particles.

[0018] Suitable surface postcrosslinkers are, for example, polyfunctional amines, polyfunctional amidoamines, polyfunctional epoxides, difunctional or polyfunctional alcohols, β-hydroxyalkylamides, cyclic carbonates, 2-oxazolidinone and derivatives thereof, bis-2-oxazolidinone and poly-2-oxazolidinone, 2-oxotetrahydro-1,3-oxazine and derivatives thereof, cyclic ureas, bicyclic amide acetals, oxetanes, cyclic ureas and morpholine-2,3-dione and derivatives thereof.

[0019] Before the thermal surface postcrosslinking, hydrogen peroxide is added to the polymer particles in an amount of preferably 0.016 to 0.080% by weight, more preferably 0.018 to 0.065% by weight, most preferably 0.020 to 0.050% by weight, based on the polymer particles.

[0020] The temperature of the polymer particles during the thermal surface postcrosslinking is preferably from 110 to 220° C., more preferably from 120 to 200° C., most preferably from 130 to 190° C. Lower temperatures are also possible during the heating of the polymer particles.

[0021] The residence time of the polymer particles in the thermal surface postcrosslinking is preferably from 10 to 120 minutes, more preferably from 15 to 90 minutes, most preferably from 20 to 60 minutes.The residence time is the residence time of the polymer particles in the apparatus for the thermal surface postcrosslinking.

[0022] In a preferred embodiment of the present invention, the monomer solution contains the polymerization inhibitor in an amount of preferably 0.001 to 0.020 wt %, more preferably 0.002 to 0.015 wt %, most preferably 0.004 to 0.010 wt %, based on the acrylic acid before neutralization.

[0023] Suitable polymerization inhibitors are, for example, hydroquinone monomethyl ether (MEHQ) and α-tocopherol (vitamin E). Hydroquinone monomethyl ether (MEHQ) is preferred.

[0024] In a preferred embodiment of the invention, the chelating agent is added to the polymer particles during or after cooling in an amount of preferably 0.005 to 1.0 wt. %, more preferably 0.010 to 0.7 wt. %, most preferably 0.015 to 0.5 wt. % (based on the polymer particles).

[0025] Suitable chelating agents are, for example, citric acid, tartaric acid, iminodiacetic acid, hydroxyethyliminodiacetic acid, nitrilotriacetic acid, nitrilotripropionic acid, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraaminehexaacetic acid, N,N-bis(2-hydroxyethyl)glycine, trans-1,2-diaminocyclohexanetetraacetic acid and 1-hydroxyethane-1,1-diphosphonic acid and its salts. 1-Hydroxyethane-1,1-diphosphonic acid and / or its salts are preferred.

[0026] Surface post-crosslinking is performed by heating. No irradiation with active energy rays is required.

[0027] The present invention is based on the finding that the long-term color stability of superabsorbent polymers can be improved by treatment with hydrogen peroxide prior to thermal post-crosslinking. Excessively high amounts of hydrogen peroxide have a negative impact on the absorption under high load (AUHL).

[0028] Adding hydrogen peroxide or using other peroxides after thermal post-crosslinking is not effective.

[0029] The present invention also provides superabsorbent polymer particles obtainable by the process of the present invention.

[0030] The superabsorbent polymer particles prepared by the process of the present invention preferably have a centrifuge retention capacity (CRC) of at least 40 g / g, more preferably at least 41 g / g, most preferably at least 42 g / g. The superabsorbent polymer particles typically have a centrifuge retention capacity (CRC) of less than 60 g / g.

[0031] The superabsorbent polymer particles prepared by the process of the present invention preferably have an absorption capacity under high load (AUHL) of at least 20 g / g, more preferably at least 22 g / g, most preferably at least 24 g / g. The absorption capacity under high load (AUHL) of the superabsorbent polymer particles is typically less than 50 g / g.

[0032] The superabsorbent polymer particles prepared by the method of the present invention have a yellowness index (YI) of YID1925 (2 / C) of preferably not more than 54, more preferably not more than 52, and most preferably not more than 50 after aging at 70°C and 80% relative humidity for 14 days.

[0033] The preparation of the superabsorbent is described in detail below:

[0034] Superabsorbents are prepared by polymerizing a monomer solution and are generally insoluble in water.

[0035] Suitable crosslinkers b) are compounds having at least two groups suitable for crosslinking. Such groups are, for example, ethylenically unsaturated groups which can be free-radically polymerized into the polymer chain, and functional groups which can form covalent bonds with the acid groups of acrylic acid. In addition, polyvalent metal salts which can form coordinate bonds with at least two acid groups of acrylic acid are also suitable as crosslinkers b).

[0036] Crosslinkers b) are preferably compounds having at least two polymerizable groups which can be polymerized free-radically into the polymer network. Suitable crosslinkers b) are, for example, ethylene glycol dimethacrylate, diethylene glycol diacrylate, polyethylene glycol diacrylate, allyl methacrylate, trimethylolpropane triacrylate, triallylamine, tetraallyl ammonium chloride, tetraallyloxyethane as described in EP 0 530 438 A1; diacrylates and triacrylates as described in EP 0 547 847 A1, EP 0 559 476 A1, EP 0 632 068 A1, WO 93 / 21237 A1, WO 2003 / 104299 A1, WO 2003 / 104300 A1, WO 2003 / 104301 A1 and DE 103 31 450 A1; diacrylates and triacrylates as described in DE 103 31456 A1 and DE 103 55 401A1, which, in addition to the acrylate groups, further contain ethylenically unsaturated groups; or crosslinker mixtures such as described in DE 195 43 368A1, DE 196 46 484A1, WO 90 / 15830A1 and WO 2002 / 032962 A2.

[0037] Preferred crosslinkers b) are pentaerythritol triallyl ether, tetraallyloxyethane, methylenebismethacrylamide, 15-tuply ethoxylated trimethylolpropane triacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate and triallylamine.

[0038] Very particularly preferred crosslinkers b) are diacrylates or triacrylates which have been esterified with acrylic acid or methacrylic acid to give polyethoxylated glycerol and / or polypropoxylated glycerol, as described, for example, in WO 03 / 104301 A1. Diacrylates and / or triacrylates of 3- to 10-tuply ethoxylated glycerol are particularly advantageous. Very particularly preferred are diacrylates or triacrylates of 1- to 5-tuply ethoxylated and / or propoxylated glycerol. Most preferred are triacrylates of 3- to 5-tuply ethoxylated and / or propoxylated glycerol, in particular triacrylates of 3-tuply ethoxylated glycerol.

[0039] The amount of crosslinker b) used is preferably 0.05 to 1.5% by weight, more preferably 0.1 to 1% by weight, most preferably 0.3 to 0.6% by weight, each based on acrylic acid before neutralization. With increasing crosslinker content, the centrifuge retention capacity (CRC) decreases and at 21.0 g / cm 2 The absorption under pressure passes through a maximum value.

[0040] The initiators c) used may be all compounds which generate free radicals under the polymerization conditions, for example thermal initiators, redox initiators, photoinitiators. Suitable redox initiators are sodium peroxodisulfate / ascorbic acid, hydrogen peroxide / ascorbic acid, sodium peroxodisulfate / sodium bisulfite and hydrogen peroxide / sodium bisulfite. Preference is given to using mixtures of thermal initiators and redox initiators, for example sodium peroxodisulfate / hydrogen peroxide / ascorbic acid. However, the reducing component used is preferably disodium 2-hydroxy-2-sulfinatoacetate or a mixture of disodium 2-hydroxy-2-sulfinatoacetate, disodium 2-hydroxy-2-sulfinatoacetate and sodium bisulfite. Such mixtures may be used in combination with the initiators c) of the present invention. FF6 and FF7 (Brüggemann Chemicals; Heilbronn; Germany) was obtained.

[0041] Typically, an aqueous monomer solution is used. The water content of the aqueous monomer solution is preferably 40 to 75% by weight, more preferably 45 to 70% by weight, most preferably 50 to 65% by weight. A monomer suspension, i.e. a monomer solution containing an excess of sodium acrylate, can also be used. With increasing water content, the energy requirement in the subsequent drying step increases, and with decreasing water content, the heat of polymerization cannot be removed sufficiently.

[0042] To achieve optimal effect, preferred inhibitors require dissolved oxygen. Therefore, before polymerization, the monomer solution can be freed of dissolved oxygen by inertization (i.e., flowing an inert gas, preferably nitrogen or carbon dioxide, through it). Before polymerization, the oxygen content of the monomer solution is preferably reduced to less than 1 ppm by weight, more preferably less than 0.5 ppm by weight, and most preferably less than 0.1 ppm by weight.

[0043] For better control of the polymerization reaction, all known chelating agents can optionally be added to the monomer solution or suspension or to the starting material thereof. Suitable chelating agents are, for example, phosphoric acid, diphosphoric acid, triphosphoric acid, polyphosphoric acid, citric acid, tartaric acid or their salts.

[0044] Other suitable examples are iminodiacetic acid, hydroxyethyliminodiacetic acid, nitrilotriacetic acid, nitrilotripropionic acid, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraaminehexaacetic acid, N,N-bis(2-hydroxyethyl)glycine and trans-1,2-diaminocyclohexanetetraacetic acid and salts thereof. The amount used is generally 1 to 30 000 ppm, preferably 10 to 1000 ppm, preferably 20 to 600 ppm, more preferably 50 to 400 ppm, most preferably 100 to 300 ppm, based on monomer a).

[0045] The monomer solution is polymerized. Suitable reactors are, for example, kneading reactors or belt reactors. In a kneader, the polymer gel formed in the polymerization of the aqueous monomer solution or suspension is comminuted continuously, for example by counter-rotating stirring shafts, as described in WO 2001 / 038402 A1. Polymerization on belts is described, for example, in DE 38 25 366 A1 and US 6,241,928. Polymerization in a belt reactor forms a polymer gel which has to be comminuted in a further process step, for example in an extruder or a kneader.

[0046] In order to improve the drying properties, the comminuted polymer gel obtained by means of a kneader can additionally be subjected to extrusion.

[0047] The acid groups of the resulting polymer gel are usually partially neutralized. Neutralization is preferably carried out at the monomer stage. This is usually achieved by mixing in a neutralizing agent as an aqueous solution or preferably also in solid form. The degree of neutralization is preferably 50 to 85 mol %, more preferably 60 to 80 mol %, most preferably 65 to 75 mol %, for which conventional neutralizing agents can be used, preferably alkali metal hydroxides, alkali metal oxides, alkali metal carbonates or alkali metal hydrogencarbonates and mixtures thereof. In addition to alkali metal salts, ammonium salts can also be used. Particularly preferred alkali metals are sodium and potassium, very particularly preferably sodium hydroxide, potassium hydroxide and mixtures thereof.

[0048] The resulting polymer gel is dried. The dryer is not subject to any restrictions. However, the drying of the polymer gel is preferably carried out using a belt dryer until the residual moisture content is preferably 0.5 to 10% by weight, more preferably 1 to 7% by weight, most preferably 2 to 5% by weight, the residual moisture content being determined by the test method No. WSP 230.2 (05) "Mass Loss Upon Heating" recommended by EDANA. In the case of a too high residual moisture content, the glass transition temperature T of the dried polymer gel is gIn the case of a residual moisture content that is too low, further processing is very difficult. In the case of a residual moisture content that is too low, the dried polymer gel is too brittle and, in the subsequent grinding step, a large amount of undesirable polymer particles with too low a particle size ("fines") is obtained. The solids content of the gel before drying is preferably 25 to 90% by weight, more preferably 35 to 70% by weight, most preferably 40 to 60% by weight. However, a fluidized bed dryer or a paddle dryer can also be optionally used for drying purposes.

[0049] Subsequently, the dried polymer gel is ground and classified. The apparatus used for grinding may generally be a single-stage or multi-stage roller mill, preferably a two-stage or three-stage roller mill, a pin mill, a hammer mill or a vibration mill.

[0050] The average particle size of the polymer particles removed as the product fraction is preferably at least 200 μm, more preferably 250 to 600 μm, very particularly 300 to 500 μm. The average particle size of the product fraction can be determined by the test method No. WSP 220.2 (05) "Particle Size Distribution" recommended by EDANA, in which the mass fractions of the sieves are plotted in cumulative form and the average particle size is determined from the diagram. The average particle size here is the value of the mesh size that gives a cumulative 50% by weight.

[0051] The proportion of particles having a particle size of at least 150 μm is preferably at least 90% by weight, more preferably at least 95% by weight, most preferably at least 98% by weight.

[0052] Polymer particles with a particle size that is too small reduce the saline flow conductivity (SFC). Therefore, the proportion of polymer particles that are too small ("fines") should be low.

[0053] Therefore, the polymer particles which are too small are usually removed and recycled into the process. This is preferably done before, during or after the polymerization (i.e. before drying of the polymer gel). Before or during recycling, the polymer particles which are too small can be moistened with water and / or an aqueous surfactant.

[0054] It is also possible to remove the too small polymer particles in a subsequent process step, for example after a surface post-crosslinking step or another coating step. In this case, the recycled too small polymer particles are surface post-crosslinked or coated in another way, for example with fumed silica or precipitated silica.

[0055] When a kneading reactor is used for the polymerization, the undersized polymer particles are preferably added during the last third of the polymerization.

[0056] If too small polymer particles are added at a very early stage (for example actually to the monomer solution), the centrifuge retention capacity (CRC) of the resulting superabsorbent is reduced. However, this can be compensated, for example, by adjusting the amount of crosslinker b).

[0057] When too small polymer particles are added at a very late stage (e.g., until a device connected downstream of the polymerization reactor, such as an extruder), it is very difficult to incorporate the too small polymer particles into the resulting polymer gel. However, insufficiently incorporated too small polymer particles are separated again from the dried polymer gel during grinding and are therefore removed again during classification, and the amount of too small polymer particles to be recycled increases.

[0058] The proportion of particles having a particle size of at most 850 μm is preferably at least 90% by weight, more preferably at least 95% by weight, most preferably at least 98% by weight.

[0059] The proportion of particles with a particle size of at most 600 μm is preferably at least 90% by weight, more preferably at least 95% by weight, most preferably at least 98% by weight.

[0060] Polymer particles with too large a particle size reduce the free swelling rate (FSR). Therefore, the proportion of polymer particles with too large a particle size should also be small.

[0061] Therefore, oversized polymer particles are usually removed and recycled into the grinding of the dried polymer gel.

[0062] However, it is also possible to dropletize the aqueous monomer solution and polymerize the droplets obtained in a heated carrier gas stream. The process steps of polymerization and drying can be combined here, as described in WO 2008 / 052971 A1 and WO 2011 / 026876 A1.

[0063] For this purpose, the monomer solution is metered into the reaction chamber in the form of droplets through at least one orifice. The orifice may be, for example, in a dropletizer plate.

[0064] A droplet plate is a plate with at least one hole through which the liquid passes from above. The droplet plate or the liquid may be oscillated, which produces a train of ideally monodisperse droplets at each hole on the underside of the droplet plate. In a preferred embodiment, the droplet plate is not oscillated.

[0065] The number and size of the holes are selected according to the desired capacity and droplet size. The droplet diameter is generally 1.9 times the hole diameter. It is important here that the liquid to be dropletized does not pass through the hole too quickly and that the pressure drop across the hole is not too large. Otherwise, the liquid is not dropletized, but rather the liquid jet is dispersed (sprayed) due to the high kinetic energy. The Reynolds number based on the flux per hole and the pore size is preferably less than 2000, more preferably less than 1600, particularly preferably less than 1400 and most preferably less than 1200.

[0066] The droplet plate preferably has at least 5, more preferably at least 25, most preferably at least 50 holes, and preferably up to 750, more preferably up to 500, most preferably up to 250 holes. The diameter of the holes is selected according to the desired droplet size.

[0067] The diameter of the pores is preferably from 50 to 500 μm, more preferably from 100 to 300 μm, most preferably from 150 to 250 μm.

[0068] The temperature of the monomer solution when passing through the holes is preferably 5 to 80°C, more preferably 10 to 70°C, most preferably 30 to 60°C.

[0069] The pore spacing is preferably 10 to 50 mm, more preferably 12 to 40 mm, most preferably 15 to 30 mm. Too small a pore spacing may result in the formation of agglomerates.

[0070] The carrier gas flows through the polymerization reactor. The carrier gas can be conducted through the reaction chamber in the same direction or in the opposite direction (preferably in the same direction, i.e. from the bottom upwards) as the freely falling droplets of the monomer solution. After a pass, the carrier gas is preferably at least partially, preferably to an extent of at least 50%, more preferably to an extent of at least 75%, recirculated into the reaction chamber as cycle gas. Typically, a portion of the carrier gas is discharged after each pass, preferably up to 10%, more preferably up to 3%, most preferably up to 1%.

[0071] The oxygen content of the carrier gas is preferably from 0.5 to 15% by volume, more preferably from 1 to 10% by volume, most preferably from 2 to 7% by volume.

[0072] In addition to oxygen, the carrier gas preferably comprises nitrogen. The nitrogen content of the carrier gas is preferably at least 80% by volume, more preferably at least 90% by volume, and most preferably at least 95% by volume. Other suitable carrier gases are carbon dioxide, argon, xenon, krypton, neon and helium. Mixed gases may also be used. The carrier gas may also contain steam and / or acrylic acid vapor.

[0073] The gas velocity is preferably set so that the flow in the polymerization reactor is directional, e.g. there is no convection against the general flow direction, and is generally 0.1 to 2.5 m / s, preferably 0.3 to 1.5 m / s, more preferably 0.5 to 1.2 m / s, particularly preferably 0.6 to 1.0 m / s, most preferably 0.7 to 0.9 m / s.

[0074] The carrier gas flowing through the reactor is suitably preheated to the reaction temperature upstream of the reactor.

[0075] Advantageously, the gas inlet temperature is adjusted so that the gas outlet temperature (i.e. the temperature at which the carrier gas leaves the reaction chamber) is typically 90 to 150°C, preferably 100 to 140°C, more preferably 105 to 135°C, particularly preferably 110 to 130°C, most preferably 115 to 125°C.

[0076] The reaction can be carried out under elevated or reduced pressure. Preference is given to reduced pressures down to 100 mbar relative to ambient pressure.

[0077] The reaction tail gas (i.e. the gas leaving the reaction chamber) can be cooled, for example, in a heat exchanger. This condenses water and unconverted monomers a). Thereafter, the reaction tail gas can be at least partially reheated and recirculated into the reactor as cycle gas. A portion of the reaction tail gas can be discharged and replaced by fresh carrier gas, in which case water and unconverted monomers a) present in the reaction tail gas can be removed and recirculated.

[0078] Particular preference is given to integrated heating systems, which means that some of the waste heat from the exhaust gas cooling is used to heat the cycle gas.

[0079] The reactor can be trace heated. The trace heating is adjusted so that the wall temperature is at least 5°C higher than the temperature inside the reactor and condensation on the reactor wall is reliably prevented.

[0080] The reaction product is subsequently subjected to thermal aftertreatment and optionally dried to the desired water content.

[0081] In order to improve the properties, the polymer particles (base polymer) are subsequently subjected to thermal surface post-crosslinking. Suitable surface post-crosslinking agents are compounds containing groups that can form covalent bonds with at least two acid groups of the polymer particles. Suitable compounds are, for example, polyfunctional amines, polyfunctional amidoamines, polyfunctional epoxides as described in EP 0 083 022 A2, EP 0 543 303 A1 and EP 0 937 736 A2, bifunctional alcohols or polyfunctional alcohols as described in DE 33 14 019 A1, DE 35 23 617 A1 and EP 0 450 922 A2, or beta-hydroxyalkylamides as described in DE 102 04 938 A1 and US 6,239,230.

[0082] In addition, as suitable surface post-crosslinking agents, DE 40 20 780 C1 describes cyclic carbonates; DE 198 07502 A1 describes 2-oxazolidinone and its derivatives, such as 2-hydroxyethyl-2-oxazolidinone; DE 198 07 992 C1 describes bis-2-oxazolidinone and poly-2-oxazolidinone; DE 198 54573 A1 describes 2-oxotetrahydro-1,3-oxazine and its derivatives; DE 198 54 574 A1 describes N-acyl-2-oxazolidinone; DE 102 04 937 A1 describes cyclic ureas; DE 10334 584 A1 describes bicyclic amide acetals; EP 1 199 327 A2 describes oxetanes and cyclic ureas and WO 2003 / 031482 A1 describes morpholine-2,3-dione and its derivatives.

[0083] Preferred surface postcrosslinkers are ethylene carbonate, ethylene glycol diglycidyl ether, reaction products of polyamides with epichlorohydrin, and mixtures of propylene glycol and 1,4-butanediol.

[0084] Very particularly preferred surface postcrosslinkers are 2-hydroxyethyloxazolidin-2-one, oxazolidin-2-one and 1,3-propylene glycol.

[0085] In addition, it is also possible to use surface postcrosslinkers which comprise additional polymerizable ethylenically unsaturated groups, as described in DE 37 13 601 A1.

[0086] The amount of surface postcrosslinkers is preferably 0.005 to 5% by weight, more preferably 0.01 to 2% by weight, most preferably 0.015 to 1% by weight, based in each case on the polymer particles.

[0087] In a preferred embodiment of the invention, polyvalent cations are applied to the particle surface in addition to the surface postcrosslinkers before, during or after the surface postcrosslinking.

[0088] Polyvalent cations that can be used in the process of the invention are, for example, divalent cations such as zinc, magnesium, calcium, iron and strontium; trivalent cations such as aluminum, iron, chromium, rare earth and manganese; tetravalent cations such as titanium and zirconium. Possible counterions are chloride, bromide, sulfate, hydrogensulfate, carbonate, hydrogencarbonate, nitrate, phosphate, hydrogenphosphate, dihydrogenphosphate and carboxylates (e.g. acetate and lactate). Aluminum sulfate and aluminum lactate are preferred. In addition to metal salts, polyamines can also be used as polyvalent cations.

[0089] The polyvalent cation is used in an amount of, for example, 0.001 to 1.5% by weight, preferably 0.005 to 1% by weight, and more preferably 0.02 to 0.8% by weight, based on the polymer particles.

[0090] The surface post-crosslinking is usually carried out by spraying a solution of the surface post-crosslinking agent onto the dried polymer particles. After spraying, the polymer particles coated with the surface post-crosslinking agent are thermally dried, and the surface post-crosslinking reaction can be carried out before or during drying.

[0091] The spray application of the surface postcrosslinker solution is preferably carried out in mixers with moving mixing tools, such as screw mixers, disk mixers and paddle mixers. Particular preference is given to horizontal mixers, such as paddle mixers; very particular preference is given to vertical mixers. Horizontal mixers differ from vertical mixers in the position of the mixing shaft, i.e. horizontal mixers have a horizontally mounted mixing shaft and vertical mixers have a vertically mounted mixing shaft. Suitable mixers are, for example, horizontal Ploughshare mixer (Geb. Maschinenbau GmbH; Paderborn; Germany), Vrieco-Nauta continuous mixer (Hosokawa Micron BV; Doetinchem; the Netherlands), Processall Mixmill mixer (Processall Incorporated; Cincinnati; USA), and Schugi (Hosokawa Micron BV; Doetinchem; The Netherlands). However, it is also possible to spray on the surface postcrosslinker solution in a fluidized bed.

[0092] The surface postcrosslinker is generally used in the form of an aqueous solution. The penetration depth of the surface postcrosslinker in the polymer particles can be adjusted via the content of the nonaqueous solvent and the total amount of the solvent.

[0093] When only water is used as solvent, a surfactant is advantageously added. This improves the wetting behavior and reduces the tendency to form lumps. However, it is preferred to use mixed solvents, such as isopropanol / water, 1,3-propylene glycol / water and propylene glycol / water, wherein the mixing ratio is preferably 20:80 to 40:60 by mass.

[0094] The thermal surface postcrosslinking is preferably carried out in a contact dryer, more preferably in a paddle dryer, most preferably in a tray dryer. Suitable dryers are, for example, Hosokawa Horizontal paddle dryer (HosokawaMicron GmbH; Leingarten; Germany), Hosokawa Tray dryers (Hosokawa Micron GmbH; Leingarten; Germany) and Nara paddle dryers (NARA Machinery Europe; Frechen; Germany). In addition, fluidized bed dryers can also be used.

[0095] Surface postcrosslinking can be carried out in the mixer itself by means of a heating jacket or by blowing in warm air. Also suitable are downstream dryers, for example tray dryers, rotary tube furnaces or heatable screws. It is particularly advantageous to carry out mixing and drying in a fluidized bed dryer.

[0096] The surface postcrosslinking temperature range is preferably from 110 to 220° C., more preferably from 120 to 200° C., most preferably from 130 to 190° C. The residence time of the polymer particles in the thermal surface postcrosslinking is preferably from 10 to 120 minutes, more preferably from 15 to 90 minutes, most preferably from 20 to 60 minutes.

[0097] Subsequently, the surface postcrosslinked polymer particles can be fractionated again, and too small and / or too large polymer particles can be removed and recirculated into the process.

[0098] To further improve the properties, the surface postcrosslinked polymer particles can be coated or remoistened.

[0099] Remoistening is preferably carried out at 30 to 80° C., more preferably at 35 to 70° C., most preferably at 40 to 60° C. At too low a temperature, the superabsorbent tends to form lumps, while at higher temperatures the water evaporates already to a significant extent. The amount of water used for remoistening is preferably 1 to 15% by weight, more preferably 2 to 10% by weight, most preferably 3 to 5% by weight, based on the polymer particles. Remoistening increases the mechanical stability of the polymer particles and reduces their tendency to become electrostatically charged.

[0100] Suitable coatings for increasing the free swelling rate and the saline flow conductivity (SFC) are, for example, inorganic inert substances (e.g. water-insoluble metal salts), organic polymers, cationic polymers and divalent or polyvalent metal cations. Suitable coatings for dust binding are, for example, polyols. Suitable coatings for reducing the undesirable tendency of the polymer particles to agglomerate are, for example, fumed silica (e.g. 200), or precipitated silica (e.g. D17), and surfactants (e.g. 20).

[0101] method:

[0102] Unless otherwise stated, the measurements shall be carried out at an ambient temperature of 23±2° C. and a relative atmospheric humidity of 50±10%. The superabsorbent polymers shall be mixed thoroughly prior to the measurements.

[0103] Residual monomer (RAA)

[0104] The residual monomers in the superabsorbent polymer particles are determined by the EDANA recommended test method No. WSP 210.2 (04) “Determination of the Amount of Residual Monomers in Superabsorbent Materials”.

[0105] Particle size distribution

[0106] The particle size distribution of the superabsorbent polymer particles is determined by the test method No. WSP 220.2 (05) "Determination of Polyacrylate Superabsorbent Powders and Particle Size Distribution-Sieve Fractionation" recommended by EDANA.

[0107] Roundness

[0108] use The roundness was measured using a 3001L particle analyzer (Microtrac Europe GmbH; Meerbusch; Germany). The roundness is defined as

[0109]

[0110] Where A is the cross-sectional area and U is the cross-sectional perimeter of the polymer particle. The roundness is the volume average roundness.

[0111] For the measurement, the superabsorbent polymer particles are introduced through a funnel and conveyed into a falling shaft with a metering channel. As the particles fall through the light wall, they are selectively recorded by a camera. The recorded images are evaluated by the software according to the selected parameters.

[0112] Water content (MC)

[0113] The water content of the superabsorbent polymer particles is determined by the EDANA recommended test method No. WSP230.2 (05) "Moisture Content-Weight Loss Upon Heating".

[0114] Centrifuge Retention Capacity (CRC)

[0115] The centrifuge retention capacity of the superabsorbent polymer particles is determined by the test method No. WSP 241.2 (05) "Gravimetric Determination of Fluid Retention Capacity in Saline Solution After Centrifugation" recommended by EDANA, wherein for higher values ​​of the centrifuge retention capacity, a larger Tea bags (teabags) .

[0116] Absorption Under Load (AUL)

[0117] The absorption capacity of the superabsorbent polymer particles under load is determined by the EDANA recommended test method No. WSP242.2 (05) "Gravimetric Determination of Absorption Under Pressure".

[0118] Absorption under high load (AUHL)

[0119] The determination of the absorption capacity of superabsorbent polymer particles under high load is similar to the test method No. WSP 242.2 (05) "Gravimetric Determination of Absorption Under Pressure" recommended by EDANA, except that a 49.2 g / cm 2 The weight is not 21.0g / cm 2 weight.

[0120] Flow Rate

[0121] The flow rate of the superabsorbent polymer particles is determined by the EDANA recommended test method No. WSP 250.2 (05) "Gravimetric Determination of Flowrate".

[0122] Bulk density

[0123] The bulk density of the superabsorbent polymer particles is determined by the EDANA recommended test method No. WSP 260.2 (05) "Gravimetric Determination of Density".

[0124] Extractable (extended 16 hours)

[0125] The content of extractable components in the superabsorbent polymer particles is determined by the test method No. WSP270.2 (05) "Determination of Extractable Polymer Content by Potentiometric Titration" recommended by EDANA.

[0126] Agglomeration (40℃ / 80%rh / 1h)

[0127] 5 g of superabsorbent polymer particles were placed in an aluminum weighing pan (57 mm × 15 mm) and stored at 40 ° C and 80% relative humidity for 1 hour. The sample was cooled to ambient temperature and weighed. After sieving on a 1.68 mm aperture sieve (ASTM No. 12, the diameter of the sieve is > 57 mm and < 100 mm), the amount of particles passing through the sieve was weighed to determine the mass of the unagglomerated polymer particles. The sieving process is described as follows:

[0128] Carefully pick up the aluminum pan containing the hydrated polymer and hold it upright in one hand. Place the sieve pan assembly upside down on the weigh pan and in one continuous motion gently flip the sieve pan and weigh pan containing the polymer over so that the weigh pan is now flipped over the top of the sieve. Add the lid to the sieve and over the aluminum weigh pan and place the assembly in the sieve shaker. In Vibratory Sieve Shaker AS200 control The sieve assembly was vibrated at an amplitude of 0.20 mm for one minute.

[0129] The percentage of particles that do not agglomerate is then determined by the following formula:

[0130]

[0131] Where W d is the weight of the aluminum plate, W HYD is the weight of the hydrated polymer plus the aluminum pan before sieving, W PAN is the weight of the collection tray, W UNC is the weight of the collection tray and the hydrated polymer.

[0132] Color value (CIE color number [L, a, b])

[0133] The measurement of color values ​​was done according to the CIELAB procedure (Hunterlab, Vol. 8, 1996, No. 7, pp. 1-4) using a colorimeter model "LabScan XE Spectrometer" (HunterLab; Reston; USA). Colors are represented by the coordinates L, a and b of a three-dimensional system. L represents lightness, L=0 is black and L=100 is white. The values ​​of a and b describe the position of the color on the color axis red / green or yellow / blue, respectively, where positive a values ​​represent red, negative a values ​​represent green, positive b values ​​represent yellow, and negative b values ​​represent blue.

[0134] The yellowness index (YI) of YA D1925 (2 / C) is measured according to ASTM D-1925, 2 deg. / III.° C. The higher the value, the darker and more yellow the color.

[0135] use Tissue culture dish The test was performed on a Tissue Culture Dish (35 mm in diameter and 10 mm in height) and a 0.5 inch opening orifice plate.

[0136] The color value is measured in accordance with the tristimulus method of DIN 5033-6. Example

[0137] Example 1 (Base Polymer)

[0138] The implementation of this example is similar to Example 1 in WO 2016 / 134905 A1.

[0139] As shown in Figure 1 of WO 2016 / 134905 A1, the process is carried out in a co-current spray drying device with an integrated fluidized bed (27). The height of the reaction zone (5) is 22 m and the diameter is 3.4 m. The diameter of the internal fluidized bed (IFB) is 3 m and the weir height is 0.25 m.

[0140] The drying gas is fed through the gas distributor (3) at the top of the spray dryer. The drying gas is partially recycled (drying gas loop) through a cyclone separator and a condensation tower (12) as a dust removal device (9). The drying gas is nitrogen, which contains 1% to 4% by volume of residual oxygen based on volume. Before the start of polymerization, the drying gas loop is filled with nitrogen until the residual oxygen is less than 4% by volume. The gas velocity of the drying gas in the reaction zone (5) is 0.79 m / s. The pressure inside the spray dryer is 4 mbar lower than the ambient pressure.

[0141] As shown in Figure 3 of WO 2016 / 134905 A1, the temperature of the gas leaving the reaction zone (5) is measured at three points around the end of the cylindrical part of the spray dryer. The average temperature (spray dryer outlet temperature) is calculated using three single measurements (43). The drying gas loop is heated and the quantitative addition of the monomer solution is started. From this point on, the outlet temperature of the spray dryer is controlled to 114°C by adjusting the gas inlet temperature via a heat exchanger (20). The gas inlet temperature is 167°C.

[0142] The product accumulates in the internal fluidized bed (27) until the weir height is reached. A regulated internal fluidized bed gas at a temperature of 105°C is fed to the internal fluidized bed (27) via the pipeline (25). The gas velocity of the internal fluidized bed gas in the internal fluidized bed (27) is 0.65 m / s. The product residence time is 150 min. The temperature of the superabsorbent polymer particles in the internal fluidized bed (27) is 71°C.

[0143] The tail gas of the spray dryer is filtered in a cyclone separator (9) as a dust removal device (9) and sent to a condensation tower (12) for quenching / cooling. Excess water is pumped out of the condensation tower (12) by controlling the (constant) filling level in the condensation tower (12). The water in the condensation tower (12) is cooled by a heat exchanger (13) and pumped countercurrent to the gas. The water in the condensation tower (12) is set to an alkaline pH by metering sodium hydroxide solution to flush out acrylic acid vapors.

[0144] The gas leaving the condensation tower (12) is divided into a drying gas inlet pipe (1) and a conditioned internal fluidized bed gas (25). The gas temperature is controlled by heat exchangers (20) and (22). The hot drying gas is fed to the co-current spray dryer via a gas distributor (3). The gas distributor (3) consists of a set of pressure drop plates providing a pressure drop of 2 to 4 mbar depending on the amount of drying gas.

[0145] The product is discharged from the internal fluidized bed (27) through a rotary valve (28) into a screen (29). The screen (29) is used to screen out rejects / agglomerates with a particle size greater than 800 μm.

[0146] The monomer solution is prepared by mixing acrylic acid first with 3-tuply ethoxylated glycerol triacrylate (internal crosslinker), secondly with a 37.3% by weight sodium acrylate solution and then with an aqueous solution of 1-hydroxyethane-1,1-diphosphonic acid disodium (HDPA). The temperature of the resulting monomer solution is controlled at 10° C. by using a heat exchanger and pumping into the loop. A filter with a mesh size of 250 μm is used in the loop after the pump. As shown in FIG. 1 of WO 2016 / 134905 A1, the initiator is metered into the monomer solution upstream of the dropper via lines (33) and (34) by means of static mixers (31) and (32). A sodium peroxodisulfate solution at a temperature of 20° C. is added via line (33), and a [2,2′-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride solution is added via line (34). Each initiator was pumped into the loop and metered into each dropper device via a control valve. A second filter device with a mesh size of 140 μm was used after the static mixer (32). To meter the monomer solution into the top of the spray dryer, three dropper devices were used, as shown in Figure 4 of WO 2016 / 134905A1.

[0147] The dropper device consists of an outer tube (47) with an opening for a dropper box (49), as shown in Figure 5 of WO 2016 / 134905 A1. The dropper box (49) is connected to an inner tube (48). For maintenance purposes, during operation of the process, the inner tube (48) with a PTFE baffle (50) as a seal at its end can be pushed into and pulled out of the outer tube (47).

[0148] The dropper box (49) has 256 holes with a diameter of 170 μm and a hole spacing of 15 mm. The dropper box (49) consists of a flow channel (56) (essentially without a retardation volume for uniform distribution of the premixed monomer solution and initiator solution) and a dropper plate (53). The dropper plate (53) has an angled configuration of 3°. The dropper plate (53) is made of stainless steel and has a length of 630 mm, a width of 128 mm, and a thickness of 1 mm.

[0149] The feed to the spray dryer consisted of 10.45 wt % acrylic acid, 33.40 wt % sodium acrylate, 0.018 wt % 3-tuply ethoxylated glycerol triacrylate, 0.108 wt % disodium 1-hydroxyethane-1,1-diphosphonate (HDPA), 0.072 wt % [2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 0.072 wt % sodium peroxodisulfate solution (15 wt % aqueous solution) and water. The degree of neutralization was 71%. The feed rate per hole was 1.4 kg / h.

[0150] The obtained superabsorbent polymer particles were analyzed. The conditions and results are summarized in Tables 1 to 3.

[0151] Example 2 (not of the present invention)

[0152] 1200 g of the water-absorbing polymer particles (base polymer) prepared in Example 1 were placed in a laboratory ploughshare mixer (MR5 type, manufactured by Gebrüder Maschinenbau GmbH; Paderborn; manufactured in Germany). A surface postcrosslinker solution was prepared by mixing 30 g of ethylene carbonate, 1.2 g of aluminum sulfate and 60 g of deionized water (as shown in Table 4) in a beaker. At a mixer speed of 200 rpm, the aqueous solution was sprayed onto the polymer particles through a nozzle within one minute. Mixing was continued for a further 5 minutes. The product was removed and transferred to another plowshare mixer (MR5 type, manufactured by Gebrüder) preheated to 150° C. After mixing for a further 40 minutes at 150° C., the product was removed from the mixer and sieved through a 850 μm sieve.

[0153] As shown in Table 8, 3 g of aluminum lactate, 25 mg of sorbitan monolaurate ( 20) and 80 g of deionized water were mixed to prepare a rewetting solution. 1000 g of this product was transferred to another plowshare mixer (MR5 type, manufactured by Gebrüder) preheated to 80°C. Maschinenbau GmbH; Paderborn; made in Germany). After reaching a final temperature of 80° C., the heating of the plowshare mixer was switched off and the aqueous rewetting solution was sprayed onto the polymer particles via a nozzle at a mixer speed of 200 rpm within 2 minutes. Mixing was continued for a further 13 minutes. The product was removed and sieved through a sieve of 850 μm.

[0154] The samples were analyzed. The formulations, conditions and results are summarized in Tables 4 and 5.

[0155] Embodiment 3 (present invention)

[0156] This example was carried out similarly to Example 2, except that 0.18 g of hydrogen peroxide was additionally added to the surface postcrosslinker solution.

[0157] Example 4 (the present invention)

[0158] This example was carried out similarly to Example 2, except that an additional 0.36 g of hydrogen peroxide was added to the surface postcrosslinker solution.

[0159] Embodiment 5 (present invention)

[0160] This example was carried out similarly to Example 2, except that 0.72 g of hydrogen peroxide was additionally added to the surface postcrosslinker solution.

[0161] Embodiment 6 (present invention)

[0162] This example was carried out similarly to Example 2, except that 1.08 g of hydrogen peroxide was additionally added to the surface postcrosslinker solution.

[0163] Example 7 (not of the present invention)

[0164] This example was carried out similarly to Example 2, except that 1.80 g of hydrogen peroxide was additionally added to the surface postcrosslinker solution.

[0165] Example 8 (not of the present invention)

[0166] This example was carried out similarly to Example 2, except that 3.60 g of hydrogen peroxide were additionally added to the surface postcrosslinker solution.

[0167] Example 9 (not of the present invention)

[0168] The implementation of this example is similar to that of Example 2, except that 0.18 g of sodium persulfate is additionally added to the surface post-crosslinker solution.

[0169] Example 10 (not of the present invention)

[0170] The implementation of this example is similar to that of Example 2, except that 0.36 g of sodium persulfate peroxide is additionally added to the surface post-crosslinker solution.

[0171] Example 11 (not of the present invention)

[0172] The implementation of this example is similar to that of Example 2, except that 0.72 g of sodium persulfate peroxide is additionally added to the surface post-crosslinker solution.

[0173] Example 12 (not of the present invention)

[0174] The implementation of this embodiment is similar to that of Embodiment 2, except that 0.15 g of hydrogen peroxide is additionally added to the remoisturizing agent solution.

[0175] Example 13 (not of the present invention)

[0176] The implementation of this embodiment is similar to that of Embodiment 2, except that 0.30 g of hydrogen peroxide is additionally added to the remoisturizing agent solution.

[0177] Example 14 (not of the present invention)

[0178] The implementation of this example is similar to that of Example 2, except that 0.60 g of hydrogen peroxide is additionally added to the remoisturizing agent solution.

[0179]

[0180]

[0181]

Claims

1. A method for preparing long-term color-stable superabsorbent polymer particles comprising the polymerization of a monomer solution comprising: a) partially neutralized acrylic acid, b) optionally at least one cross-linking agent, and c) at least one initiator; The resulting polymer gel is dried, the resulting dried polymer gel is optionally ground and classified, and the resulting polymer particles are thermally postcrosslinked and cooled; wherein a thermal postcrosslinker and 0.014 to 0.095% by weight of hydrogen peroxide, based on the polymer particles, are added to the polymer particles before the thermal postcrosslinking. 2 . The process according to claim 1 , wherein from 0.005 to 5% by weight, based on the polymer particles, of a thermal postcrosslinker are added to the polymer particles before the thermal postcrosslinking. 3 . The process according to claim 1 , wherein from 0.02 to 0.05% by weight of peroxide, based on the polymer particles, is added to the polymer particles before the thermal aftercrosslinking.

4. The method according to claim 1, wherein the temperature of the post-crosslinking is 130 to 190°C.

5. The process according to claim 1, wherein the residence time for post-crosslinking is 20 to 60 minutes. The method according to claim 1 , wherein the monomer solution contains a polymerization inhibitor.

7. The method according to claim 1, wherein the monomer solution contains 0.004 to 0.010% by weight of a polymerization inhibitor, based on acrylic acid.

8. The process according to claim 6 or 7, wherein hydroquinone monomethyl ether is used as a polymerization inhibitor.

9. The method of claim 1, wherein at least one chelating agent is added to the polymer particles during or after cooling.

10. The process according to claim 1, wherein from 0.005 to 1% by weight, based on the polymer particles, of at least one chelating agent are added to the polymer particles during or after cooling.

11. The method according to claim 9 or 10, wherein 1-hydroxyethane-1,1-diphosphonic acid and / or a salt thereof is used as the chelating agent.

12. The method according to claim 1, wherein the post-crosslinking is performed without irradiation with any active energy rays.

13. Superabsorbent polymer particles obtainable according to the process of any one of claims 1 to 12, wherein the superabsorbent polymer particles have a centrifuge retention capacity of at least 40 g / g and an absorption under high load of at least 20 g / g.

14. The superabsorbent polymer particle according to claim 13, wherein the superabsorbent polymer particle has a yellowness index of no greater than 54 after aging at 70°C and 80% relative humidity for 14 days.

15. The superabsorbent polymer particle according to claim 13 or 14, wherein the superabsorbent polymer particle has a yellowness index of not more than 50 after aging at 70°C and 80% relative humidity for 14 days.